Symbol Used in the Demon Slayer: Mugen Train Movie - Anggun Purnomo Arbi; Iddun Muhammad Hattory; Nur Kalim (STKIP PGRI SIDOARJO, 2021)
The objective of this study was to describe the symbol used in the Demon Slayer: Mugen Train the movie. Symbol, as the part of literature, can be defined as often characters, images, settings and the other elements which reflect bigger hidden ideas or message in order to build more interesting story. Viewed from its setting, this study was applied library research as it studied a movie. The subject of this study was a Japanese movie entitled “Demon Slayer: Mugen Train”. In collecting the data, there were two research instruments including: the researcher as a data collector and analyst, and the documentations. The data of this study were phenomena classified as symbols. Those data were collected from the Movie. The steps of data collections included: (1) watching movie several times, (2) reading the movie scripts.The data analysis steps in this study were identified as the decriptive analysis technique. The results of this study presented that there were som symbols found in the Demon Slayer: Mugen train movie, they were: nature symbols (flame, water, and Thunder), object symbols (word (Nichirin Sword), Hanafuda Earrings, and tomb), animal symbol (crow), and color symbols (pink, blue, black or dark, and red).